Developmental Correlates of Microcephaly - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2009)
Developmental and motor function at age 2 years of 958 children born before the 28th week of gestation were assessed at Boston and Harvard Universities and other centers, comparing those with microcephaly at birth or 2 years with children with normal head circumference.